Consumer attitudes toward bacteriophage applications to pet food - Eagan, Bailey H.; Wang, Siyun; Hall, Nathaniel; Protopopova, Alexandra (Frontiers in Veterinary Science, 2022)
This study used a two-part questionnaire to investigate consumer knowledge and attitudes toward bacteriophage applications in pet food, pet food safety, and environmental sustainability. Part 1 included questions about pet food safety, sustainability, and knowledge and attitudes toward bacteriophages. Next, participants reviewed educational materials about each, and Part 2 assessed if this increased knowledge of, or changed attitudes toward, bacteriophage application. Participants (n=80), were recruited through Amazon Mechanical Turk (MT) (n=45) and Social Media (SM) (n=35). Mean responses in Part 1 and Part 2 were compared by paired t-tests, and mean responses between MT and SM were compared by t-tests. Participants reported pet food safety is important to them (combined proportion strongly agree or agree, mean ± SD) (75/80, 94%, MT 4.66 ± 0.60, SM 4.71 ± 0.95) and are most concerned with raw pet food safety (51/80, 64%, MT 3.88 ± 0,80, SM 3.17 ± 1.40). Participants rate environmental sustainability as important (61/80, 76%, MT 3.86 ± 0.94, SM 3.97 ± 0.66); however, it is not a strong driver of pet food purchasing (26/80, 33%, MT 3.31 ± 1.25, SM 2.82 ± 0.82). Overall, data showed an increase in knowledge of bacteriophages following a review of educational material. However, in the SM group, no statistically significant difference was observed in the comfort eating food with bacteriophage additives (SM Part 1 3.37 ± 1.05, SM Part 2 3.48 ± 1.12, p=0.279), whereas the MT group did show an increase (MT Part 1 3.57 ± 1.01, MT Part 2 4.08 ± 0.92, p< 0.001). In the SM group, no statistically significant difference was observed in comfort feeding their pet food with bacteriophage additives (SM Part 1 3.40 ± 1.03, SM Part 2 3.45 ± 1.14, p=0.571), whereas the MT group did show an increase (MT Part 1 3.57 ± 0.98, MT Part 2 4.31 ± 0.84, p< 0.001). The strongest objections related to safety concerns (20/53, 38%, MT 2.83 ± 0.96, SM 3.27 ± 0.84). These results demonstrate that despite increasing knowledge, there is still hesitancy among some consumers toward bacteriophage applications in pet food.